FRI0443 Can Quantitative Chest CT Predict Interstitial Lung Disease Worsening in Systemic Sclerosis? Results from a Multi-Centre Prospective Cohort Study. (9th June 2015) - Ariani, A.; Silva, M.; Parisi, S.; Saracco, M.; Bravi, E.; De Gennaro, F.; Benini, C.; Caramaschi, P.; Lumetti, F.; Seletti, V.; Idolazzi, L.; Bodini, F.C.; et al.
Abstract : Background: Interstitial Lung Disease (ILD) is the leading cause of morbidity and mortality in Systemic Sclerosis (SSc). Forced Vital Capacity (FVC) and chest Computed Tomography (CT) are the main exams to assess ILD severity. In particular, FVC <70% is associated with a high risk of death. A visual score (VS), based on extension of fibrosis detectable at chest CT>20%, has an unfavourable prognostic value [Goh et al., 2008]. Preliminary evidence supports the usefulness of an automated quantitative CT (QCT) assessment performed with a medical software, OsiriX, in identifying patients with more severe SSc-ILD [Ariani et al. 2014] Objectives: The aim of this work is to investigate whether QCT can predict ILD-SSc radiological and functional worsening over time. Methods: One hundred forty-nine patients with SSc according to EULAR/ACR criteria underwent chest CTs and pulmonary functional tests at baseline (t0) and after 1 year (t1). A VS was evaluated for each chest CT; the quantitative assessment, in order to obtain QCT indexes (QCTI), was performed only in chest CT done in t0. Patients were clustered in 3 groups: 1) VS <20% both at t0 and t1; 2) radiological worsening (defined as the increase of the visual score, between t0 and t1, from <20% to >20% values); 3)VS>20% both at t0 and t1. A similar subdivision in other three groups was performed on the basis of FVC values (with 70% as cutoff).The Kolmogorov-Smirnov test was used to investigate QCTI distribution in the above mentioned groups. A p-value <0.05 was considered significant. Results: In group 1 (clustered according to VS variation) QCTI were different from the ones of the other two groups (p<0.001). Group 2 and 3 QCTI were not statistically different. Similar results were observed when patients were clustered according to FVC values: group1 was different from group 2 and 3 (p<0.05) but the last ones were not statistically different. Figure A shows kurtosis (one of the QCTI) distribution in the groups. Conclusions: In spite of the limitations of this study (short follow up compared with the slow ILD-SSc progression) our results support the predictivity of a QCTI in terms of future radiological and functional ILD worsening. Given its reliability and easy access, quantitative CT assessment of ILD is a promising candidate in the assessment and prognostic stratification of SSc-ILD, even in clinical practice. Disclosure of Interest: None declared